2018
DOI: 10.15688/jvolsu11.2018.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Auutophagyin Tumor Cells by Synthetic Monophenol Antioxidants: Dependence on Structure and Concentration

Abstract: The present research is devoted to the study of the relationship between the structure of the original synthetic monophenolic antioxidants and their ability to influence the activity of autophagy in tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It has been established that, in addition to antioxidant and detoxifying effects (Milaeva et al 2006), phenols and polyphenols can independently exhibit selective toxicity against tumor cells, the data was obtained from in vitro experiments (Gaynutdinov et al 2018). Synthetic monophenolic antioxidants activate autophagy and apoptotic processes in tumor cells (Menshchikova et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that, in addition to antioxidant and detoxifying effects (Milaeva et al 2006), phenols and polyphenols can independently exhibit selective toxicity against tumor cells, the data was obtained from in vitro experiments (Gaynutdinov et al 2018). Synthetic monophenolic antioxidants activate autophagy and apoptotic processes in tumor cells (Menshchikova et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of 2,6-di-tret-butylphenol group is based on our previous studies that demonstrated a potent antioxidant property of this group as well as an antitumor efficacy of substituted phenol derivatives (Gaynutdinov et al 2018;Menshchikova et al 2018). 2,6-di-tret-butylphenols are biomimetics of natural antioxidants (α-tocopherol).…”
Section: Introductionmentioning
confidence: 99%